2019
DOI: 10.2147/dddt.s185995
|View full text |Cite
|
Sign up to set email alerts
|

<p>A comparative double-blind randomized study on the effectiveness of Duloxetine and Gabapentin on painful diabetic peripheral polyneuropathy</p>

Abstract: Background: The most common cause of polyneuropathy is diabetes mellitus. Neuropathic pain is seen in 26% of diabetic population. Therapeutic techniques for this disease can become challenging. Method: This study was a prospective comparative double-blind randomized study which was conducted during an eight-week period. Totally, 104 painful diabetic peripheral polyneuropathy (PDPP) patients who had a minimum Visual Analog Scale (VAS) of 40 millimeters, received no pain-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
0
26
0
1
Order By: Relevance
“…Overall, one of the studies raised some concerns, 22 and the other two were classified as low risk. 23,24 Evidence quality assessment was based on GRADE. 18 The details are shown in Table 3.…”
Section: Studyqualityassessmentmentioning
confidence: 99%
“…Overall, one of the studies raised some concerns, 22 and the other two were classified as low risk. 23,24 Evidence quality assessment was based on GRADE. 18 The details are shown in Table 3.…”
Section: Studyqualityassessmentmentioning
confidence: 99%
“…The gabapentin group reported more adverse events, which may be because of higher than normal recommend dose (900 mg/day) used in the study. 20 Devi et al 11 evaluated clinical efficacy of gabapentin, duloxetine, and pregabalin in PDN. In this trial, the gabapentin, duloxetine, and pregabalin groups showed a significant reduction in VAS at the end of 12 weeks (P < .05) but there was no significant difference between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…In yet another study venlafaxine was found to be inferior to pregabalin in this regard [30]. Duloxetine monotherapy was found to be an equally potent agent as gabapentin for the treatment of Diabetic Polyneuropathy pain, however with much better tolerability [31]. Likewise, duloxetine showed efficacy comparable to pregabalin for the treatment of such pain [32].…”
Section: Discussionmentioning
confidence: 99%